Apuntes a la historia del cabaret político mexicano: aspectos contraculturales - Alzate, Gastón (Latin American Theatre Review, 2016)
This article provides an overview of the origins of contemporary Mexican political cabaret in Mexico City since the 1970s. It takes into consideration the historical and political context of Mexican culture and the relations between countercultural manifestations, contemporary art, para-theatrical spaces, and sexual dissidence. The article also aims to cover the most significant aspects of the incorporation of plural libertarian movements in the 1960s and 1970s into Mexican culture. This was a difficult process due to the authoritarian, long-term government of the Partido Revolucionario Institucional (PRI). The creators of contemporary Mexican political cabaret are part of a resistant popular theatrical movement that has provided an alternative critical model vis-a-vis the traditional, authoritarian, and dominant political environment of Mexico.